Nevralgia trigeminale refrattaria: un approccio efficace con radiofrequenza pulsata applicata al ganglio pterigopalatino - Refractory trigeminal neuralgia: an effective approach with pulsed radiofrequency applied to the pterygopalatine ganglion - Carmelo Costa; Marilina Schembari (Publiediting, 2016)
Trigeminal neuralgia is a neuropathic pain which involves the fifth cranial nerve. The pain is severe and paroxysmal like electric shocks and lasts from a few seconds to two minutes. Although many patients with multiple sclerosis complain of trigeminal neuralgia, its cause and mechanism are still debated. Usual therapy for trigeminal neuralgia is with antiepileptic drugs such as carbamazepine or oxcarbazepine. These medications have a good early pain relief, often, however, adverse effects force the patient to opt for the therapeutic percutaneous surgery procedures as radiofrequency trigeminal rhizotomy (CRFT) which has a high rate of early pain relief. In case CRFT were unfeasible, a pulsed radiofrequency neuromodulation procedure applied to pterygopalatine ganglion could be an effective option. We present a case of 46-year-old male suffering from I branch trigeminal neuralgia and multiple sclerosis refractory to conservative pharmacological treatment. After the technical failure of CRFT, he successfully underwent a pterygopalatine pulsed radiofrequency (PRF-PPG) procedure.